(untitled) (Revista Contexto & Educação, 2021)
This paper was based on the analyzes developed by the CNPq Research Group “Labor Economics, Education and Regional Development”, as well as the partial results of research carried out within the Graduate Program in Education: Interdisciplinary Teacher Training at the State University of Paraná, Brazil. A cutoff of the research was made in which the formative inconsistencies in the Integrated High School offered by the Federal Institute of Paraná (IFPR) were analyzed. Through a qualitative research anchored in bibliographic analyzes and in documentary sources, the professional profile of the teacher working at the IFPR was identified, as well as the concept of Professional Education proposed in the Pedagogical Projects of the courses of the modalities analyzed, courses offered in the metropolitan mesoregion from Curitiba, more precisely at the campuses of Campo Largo, Curitiba and Pinhais The results achieved revealed that the courses researched have their emphasis centered on training for the job market, even though Integrated High School is the last stage of Basic Education, therefore, of a formative character. The prevalence of the unilateral technical formative conception implies that the classes are mostly taught by bachelor teachers, with reduced workload of the disciplines of Human and Social Sciences in the Technical and Vocational Training axis.